PENGARUH KOMITMEN KERJA DAN QUALITY OF WORK LIFE (QWL) TERHADAP KEPUASAN KERJA DAN DAMPAKNYA TERHADAP KINERJA KARYAWAN PT. INDOFOOD CBP SUKSES MAKMUR CABANG JAMBI - Fathiyah Fathiyah; Ahmad Firdaus; Alex Kurnia Putra (Universitas Batanghari, 2017)
The purposes this research are to examine the influence of work commitment, Quality of Work Life (QWL), job satisfaction and employee performance. The influences of work commitment, Quality of Work Life (QWL), job satisfaction and employee performance tested both directly and indirectly by taking a sample of 80 employees. To test the variables used in research conducted a survey of employees at PT. Indofood CBP Sukses Makmur Jambi Branch. Framework of theory and data analysis is done by using Path Analysis. The results of this research indicate that the work commitment, Quality of Work Life (QWL) and job satisfaction influential support directly and indirectly to the performance of employees is positive and significant impact. The analysis tool in this research using descriptive methods and verification. Where a descriptive study using a range of scales, while in verification using path analysis. Based on the results are reflection that work commitment , Quality of Work Life (QWL), job satisfaction is an important issue to improve performance of employees. Results of the study revealed that the results related to the employee's performance is important to manage the company. Optimizing the quality of work through constant work evaluation on appropriate working standards are set, action inconsistent to individuals may lead to other negative consequences in the company, such a low performance, resistance to the organization and may indicate the behavior of disobedience the employees. Keywords: work commitment, QWL, job satisfaction and performance